CO2 Activation over Catalytic Surfaces - Álvarez, Andrea; Borges, Marta; Corral‐Pérez, Juan José; Olcina, Joan Giner; Hu, Lingjun; Cornu, Damien; Huang, Rui; Stoian, Dragos; Urakawa, Atsushi (Chemphyschem, 2017)
This article describes the main strategies to activate and convert carbon dioxide (CO2) into valuable chemicals over catalytic surfaces. Coherent elements such as common intermediates are identified in the different strategies and concisely discussed based on the reactivity of CO2 with the aim to understand the decisive factors for selective and efficient CO2 conversion. Activation and transformation of CO2 are enabled by catalytic surfaces with various forms of energetic inputs inducing characteristic reactivities. The authors summarize the physicochemical properties of CO2 and its activated forms. They also discuss key elements to be considered for efficient CO2 activation and its selective transformation to targeted products.